The low sonic boom and aerodynamic optimization with trim constraint of supersonic jet - HAO Xuan; ZHANG Qingqing; SU Cheng; LIU Fang (Hangkong gongcheng jinzhan, 2024)
The abatement of sonic boom noise level is a decisive issue for supersonic transport of next generation. The low sonic boom optimization always make the configuration to a trend of higher swept and longer distribution of the wing along the fuselage，which is unfavorable to the trim and low speed characteristics. A civil supersonic transport is researched. A parametric geometry representation method based on class function/shape function transformation（CST）is developed to describe the wing body configuration. The effects of geometry parameters on sonic boom is analyzed by supersonic linearized theory. Based on the above work，the low sonic boom and pitch moment characteristics optimization are taken for the fuselage，wing planform and twists separately and the optimal result is validated by CFD. The numerical simulation results show that compared with the basic configuration，the drag decrease 19 cts（unit of drag coefficient）and the over pressure at near-field is abated obviously without the distinct increase of pitch moment，which bring 5.1 PLdB reduction of loudness on the ground.